2009
DOI: 10.1128/jvi.01287-09
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk among the Glycoproteins Involved in Herpes Simplex Virus Entry and Fusion: the Interaction between gB and gH/gL Does Not Necessarily Require gD

Abstract: The gD, gB, and gH/gL glycoprotein quartet constitutes the basic apparatus for herpes simplex virus (HSV) entry into the cell and fusion. gD serves as a receptor binding glycoprotein and trigger of fusion. The conserved gB and gH/gL execute fusion. Central to understanding HSV entry/fusion has become the dissection of how the four glycoproteins engage in cross talk. While the independent interactions of gD with gB and gD with gH/gL have been documented, less is known of the interaction of gB with gH/gL. So far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 43 publications
6
46
0
Order By: Relevance
“…Some confounding data. A recent study, also employing BiMC, reported that gB and gH/gL can interact in the absence of gD (3). One of the problems with that study was the overexpression of the glycoproteins, and a second was the use of a mutant form of gB designed to send the protein to an abnormal cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Some confounding data. A recent study, also employing BiMC, reported that gB and gH/gL can interact in the absence of gD (3). One of the problems with that study was the overexpression of the glycoproteins, and a second was the use of a mutant form of gB designed to send the protein to an abnormal cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that, at least in HSV-1, gH/gL facilitates the activation and not the repression of gB. Complexes of gB:gH/gL have been detected from both HSV and CMV (13,14). CMV lacks gD and requires the minimal complex of gB:gH/gL for entry into fibroblasts.…”
mentioning
confidence: 92%
“…Several lines of research suggest that the subsequent step in fusion is an interaction between gH-gL and gB, with the latter glycoprotein being required for a committed and expanding fusion pore (1-3, 16, 28, 41). However, it is still unclear whether the gB and gH-gL interaction requires that gD first bind a receptor (1,3), indicating that another viable model of HSV entry may be nonsequential gD-gB-gH-gL complex formation.…”
mentioning
confidence: 99%